The problem of the inclusion of spatial dependence within the TOPSIS method - Michal Bernard Pietrzak (Institute of Economic Research (IER), 2015)
According to Tobler's first law of geography, one of the key issues in doing the regional research is considering spatial location. Therefore, the article presents a proposal for modifying the TOPSIS method, which allows the spatial dependence to be considered in the research. The composite index calculated by means of the modified TOPSIS method allows to determine the trend in the level of the development of the phenomenon under study, assuming the impact of the spatial mechanisms. The TOPSIS method defined in that way has been applied in the spatial analysis of the situation on the labour market in Poland.
Keywords: C21; E24; J01; 330; regional research; spatial econometrics; spatial dependence; TOPSIS method